2013
DOI: 10.1053/j.ajkd.2013.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Estimated GFR, Health-Related Quality of Life, and Depression Among Older Adults With Diabetes: The Diabetes and Aging Study

Abstract: Background Although chronic kidney disease (CKD) is a highly prevalent condition among older adults with diabetes, the associations between health-related quality of life (HRQOL) and severity of CKD in this population are not well understood. The objective of this study was to assess HRQOL and depressive symptoms across estimated GFR (eGFR) stages. Study Design Cross-sectional. Setting & Participants Participants included 5,805 members of Kaiser Permanente Northern California age 60 or older with diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 32 publications
4
32
0
1
Order By: Relevance
“…Similar to the Pathway Study,10 we found a significant association between albuminuria and depression, although unlike the DISTANCE survey,11 we found no significant association between reduced eGFR and depression. These cross-sectional studies, including ours, were unable to clarify the causal relationship of albuminuria and GFR with depression.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Similar to the Pathway Study,10 we found a significant association between albuminuria and depression, although unlike the DISTANCE survey,11 we found no significant association between reduced eGFR and depression. These cross-sectional studies, including ours, were unable to clarify the causal relationship of albuminuria and GFR with depression.…”
Section: Discussionsupporting
confidence: 56%
“…Among the limited number of studies, the Pathway Study consisting of 4082 US community-dwelling patients with diabetes demonstrated that PHQ-9 scores ≥10 were associated with an up to 1.5-fold increase in adjusted OR of albuminuria 10. In the Diabetes and Aging Study, an ancillary study to the Diabetes Study of Northern California (DISTANCE), the risk of depression defined as PHQ-8 scores ≥10, in which the ninth question assessing suicidal or self-injurious thoughts was eliminated from PHQ-9, was high in patients with reduced eGFR among 5805 patients with diabetes aged 60 years or older 11. Our results are in line with these studies; however, to the best of our knowledge, no previous studies have evaluated prevalence of depression, based on PHQ-9 scores or other items, in each nephropathy stage, including ESKD.…”
Section: Discussionmentioning
confidence: 99%
“…with an estimated glomerular filtration rate [eGFR] <30 ml/min/1.73 m 2 ) had more depressive symptoms than those without CKD (eGFR ≥ 60 ml/min/1.73 m 2 ). However, in only one of those studies (that included patients with diabetes) did the increased risk of depressive symptoms remain significant after adjustment for all relevant covariates [15]. Whether or not less severe forms of impaired kidney function (30 ml/min/1.73 m 2 or higher) are associated with more depressive symptoms is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, depressive symptoms are known to attenuate the urge to leave the home, resulting in physical inactivity for CKD patients [23]. In a previous study surveying approximately 6000 communitydwelling elderly, patients with stage G3-G5 CKD had double the risk of depression compared to those with stage G1-G2 CKD [24]. On the basis of these reasons, stage G3-G4 CKD may hinder acquiring appropriate physical activity after discharge.…”
Section: Discussionmentioning
confidence: 99%